Outcomes of daratumumab in the treatment of multiple myeloma: A retrospective cohort study from the Canadian Myeloma Research Group Database. (5th April 2022) - LeBlanc, Richard; Mian, Hira; Reece, Donna; Masih‐Khan, Esther; Kardjadj, Moustafa; Jimenez‐Zepeda, Victor H.; McCurdy, Arleigh; Song, Kevin; Sebag, Michael; Louzada, Martha; White, Darrell; Stakiw, Julie; et al.
Summary: Daratumumab (dara) has significantly altered the therapeutic landscape of multiple myeloma (MM), especially in the relapsed setting. This study aimed to evaluate the outcomes of dara‐containing regimens in the Canadian real‐world setting among relapsed and refractory MM available within the national Canadian Myeloma Research Group Database (CMRG‐DB). A total of 583 MM patients who received dara‐based therapy in second‐line or later treatment were included. After a median follow‐up of 17.5 months, the median progression‐free survival (PFS) and overall survival (OS) for the entire cohort were 13.1 and 32.9 months, respectively. The median PFS and OS were 23.5 and 49.1 months in second‐line treatment and decreased to 12.8 and 43.0 months in third‐line and 7.0 and 20.5 months in fourth‐line treatment respectively. Dara in monotherapy with or without corticosteroids after a median of four prior lines of therapy resulted in a median PFS of 3.9 months and a median OS of 17.1 months. The addition of bortezomib, lenalidomide or pomalidomide to dara resulted in an improved median PFS and OS of 8.3 and 26.2 months; 26.8 and 43.0 months; and 9.7 and 31.4 months respectively. These retrospective data from the CMRG‐DB suggest that outcomes are superior when dara is used in combination and in earlier lines of treatment.